A randomized controlled clinical trial on efficacy and safety of anakinra in patients with severe COVID‐19. Issue 2 (11th November 2021) - Kharazmi, Amir Behnam; Moradi, Omid; Haghighi, Mehrdad; Kouchek, Mehran; Manafi‐Rasi, Alireza; Raoufi, Masoomeh; Shoaei, ‪Simin Dokht; Hadavand, Fahimeh; Nabavi, Mahmood; Miri, Mir Mohammad; Salarian, Sara; Shojaei, Seyedpouzhia; et al.
Abstract: Introduction: Hyperinflammatory state has a role in the pathogenesis of COVID‐19. Anakinra could reduce inflammation and help to combat the condition. In this study, we aimed to assess the safety and efficacy of anakinra (PerkinRA®) in severe COVID‐19. Method: The study was an open‐label, randomized, controlled trial conducted in Imam Hossein Medical Center from May to July 2020. Patients with a confirmed diagnosis of COVID‐19 were included in this study. We administered anakinra 100 mg daily intravenously. All patients received COVID‐19 pharmacotherapy based on the represented national guideline. The need for invasive mechanical ventilation is considered the primary outcome. Results: Thirty patients were included in this study, and 15 of them received Anakinra. Nineteen patients were male (63.3%), and 11 were female (36.7%). The mean age of patients was 55.77 ± 15.89 years. In the intervention group, the need for invasive mechanical ventilation was significantly reduced compared to the control group (20.0% vs. 66.7%, p = .010). Also, these patients had a significantly lower length of hospital stay ( p = .043). No significant higher rate of infection was recorded. Conclusion: Anakinra as an immunomodulatory agent has been associated with the reduced need for mechanical ventilation in patients admitted to intensive care units because of severe COVID‐19. The medication reduced the hospital length of stay. Furthermore, no increased risk of infection was observed. Further randomized placebo‐controlled trials with a larger sample size are needed to confirm these findings. Abstract : Anakinra administration significantly reduces the need for mechanical ventilation. No increased risk of infection was observed because of anakinra use. Reduced hospitalization duration observed in patients who received anakinra.